PENGARUH KONTEN SOSMED, CUSTOMER EXPERIENCE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA SUASANA KOPI - Nur Ramadhan Sukmo AJI, (2023)
This study uses quantitative methods with the aim of proving the influence of Social Media Content, Customer experience, and product quality both directly and indirectly on Coffee Purchase Decisions. This study used 120 respondents from visitors who had come and ordered coffee as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) Social Media Content has a positive and significant effect on Purchasing Decisions, (2) Customer Experience has a positive and significant effect on Purchase Decisions, (3) Product quality has a positive and significant effect on Purchase Decisions, 4) Social Media Content , Customer Experience, and Product Quality simultaneously have a positive effect on Purchasing Decisions.